Abernethy syndrome presenting as an incidentally detected intrahepatic portosystemic shunt in an infant - Tuluce, Mahmut Esat; Sofu Öner, Yasemin; İşlek, Ali; Tümgör, Gökhan (Scientific Reports in Medicine, 2025)
Abernethy syndrome is a rare congenital anomaly in which blood from the splanchnic venous system partially or completely bypasses the liver through a portosystemic shunt and enters the systemic circulation. A subset of patients remains asymptomatic and are diagnosed incidentally, while others may present with complications such as portopulmonary hypertension, hepatopulmonary syndrome, portosystemic encephalopathy, or hepatic tumors. Early identification is important, as clinical outcomes depend on the degree of shunting and the presence of complications. In this report, we describe an asymptomatic infant diagnosed during Doppler ultrasonography, with documented spontaneous closure of the intrahepatic portosystemic shunt during follow-up and discuss the case in light of current literature to highlight the importance of careful monitoring.
Keywords: Abernethy syndrome; portosystemic shunt; intrahepatic shunt; spontaneous closure; portal venous anomaly; congenital shunt; vascular malformation